A Study of the Reality of Social Support and Ethics of the Teaching Profession among Special Needs Educational Staff in Karbala Governorate - Dawood, Dr. Linda Mahmoud (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Educational institutions play a central role in shaping behavioral and professional standards, particularly within special education settings. Specific Background: Social support and teaching ethics represent essential psychological and professional dimensions that contribute to teachers’ preparedness and responsibility in educational institutions for people with special needs. Knowledge Gap: Despite their importance, limited empirical attention has been given to examining the reality of social support and teaching ethics simultaneously among special needs educational staff in Karbala Governorate. Aims: This study aimed to identify the level of social support and the level of teaching ethics among educational and teaching staff for people with special needs in Karbala Governorate. Results: Using a descriptive survey method on a sample of 40 teachers, statistical analysis revealed that the achieved mean for social support (98.85) and teaching ethics (97.66) significantly exceeded the hypothetical mean (75), with calculated t-values of 17.28 and 16.42 respectively at a significance level of 0.05. Novelty: The study integrates psychometrically validated scales to examine both variables within a single educational context. Implications: The findings provide empirical evidence that special education staff in Karbala demonstrate strong professional ethics and social support, supporting the development of stable and responsible educational environments. Highlights: Statistical Comparison Confirmed Scores Significantly Above the Theoretical Average. Professional Conduct Indicators Reflected Strong Moral Commitment. Psychometric Testing Demonstrated Reliable Measurement Properties. Keywords: Social Support, Teaching Ethics, Special Education Staff, Educational Environment, Descriptive Survey